The Importance of Motivation in English Learning - Maili, Sjafty Nursitti NP; Sondari, Endang; Rizky, Nur (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2024)
Talking about motivation related to two things as; First Internal Motivation; refer to the students’ motivation come from their self; Second External motivation refer to how the motivation got from external such as environment at home, out of home and school. In process of learning English motivation is the role play important to make students interested in the materials that given of the teacher. Motivation really important in learning especially English learning because the high motivation make the result of student learning is too high. The methods that we used are Qualitative research that technic that the writer used is Library research. The data that we took of source such journals that discussion of teacher motivation.